Promoting a sense of security in everyday life-A case study of patients and professionals moving towards co‐production in an atrial fibrillation "learning café" - Anne‐Marie Suutari; Kristina Areskoug‐Josefsson; Sofia Kjellström; Annika M. M. Nordin; Johan Thor (Wiley, 2019)
Abstract Background An improvement initiative sought to improve care for atrial fibrillation (AF) patients; many felt insecure about how to cope with AF. Objective To reveal AF patients' and professionals' experiences of pilot‐testing a Learning Café group education programme, aimed at increasing the patients' sense of security in everyday life. Design Using an organizational case study design, we combined quantitative data (patients' sense of security) and qualitative data (project documentation; focus group interviews with five patients and five professionals) analysed using inductive qualitative content analysis. Setting AF patients and a multiprofessional team at a cardiac care unit in a Swedish district hospital. Improvement activities Two registered nurses invited AF patients and partners to four 2.5‐hour Learning Café sessions. In the first session, they solicited participants' questions about life with AF. A physician, a registered nurse and a physiotherapist were invited to address these questions in the remaining sessions. Results AF patients reported gaining a greater sense of security in everyday life and anticipating a future shift from emergency care to planned care. Professionals reported enhanced professional development, learning more about person‐centredness and gaining greater control of their own work situation. The organization gained knowledge about patient and family involvement. Conclusions The Learning Café pilot test-exemplifying movement towards co‐production through patient‐professional collaboration-generated positive outcomes for patients (sense of security), professionals (work satisfaction; learning) and the organization (better care) in line with contemporary models for quality improvement and with Self‐Determination Theory. This approach merits further testing and evaluation in other contexts.